Oxford Medicine Online 2015
DOI: 10.1093/med/9780199687039.003.0037
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in acute heart failure

Abstract: Acute heart failure continues to be a worldwide medical problem, associated with frequent readmissions, high mortality, and a profound economic impact on national health care systems. In the past decade, biomarkers have shifted the way in which acute heart failure is managed by the cardiologist. The search for the ideal biomarker to aid in the diagnosis, prognosis, and treatment of acute heart failure is ongoing. The natriuretic peptides have proved extremely useful in determining whether acute dyspnoea has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…CRS type 4 biomarkers, such as BNP and TnT, are used to diagnose cardiovascular diseases in patients with CKD [40][41][42]. Moreover, increased BNP and TnT levels are clinically used as cardiovascular mortality biomarkers [43,44]. In this study, the BNP and TnT mRNA expression levels in the heart tissues of 2K1C rats showed that their levels were reduced by the GD treatment.…”
Section: Discussionmentioning
confidence: 63%
“…CRS type 4 biomarkers, such as BNP and TnT, are used to diagnose cardiovascular diseases in patients with CKD [40][41][42]. Moreover, increased BNP and TnT levels are clinically used as cardiovascular mortality biomarkers [43,44]. In this study, the BNP and TnT mRNA expression levels in the heart tissues of 2K1C rats showed that their levels were reduced by the GD treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Although it has been shown as a strong predictive marker for a variety of cardiac disease, it is also a biomarker for other diseases including chronic obstructive pulmonary disorder, pneumonia, and pulmonary embolism [213,214]. Since MR-proADM levels have been shown to differ based on New York Heart Association (NYHA) class and severity of HF, it has the potential to help identify those patients who may benefit from more invasive therapy [215].…”
Section: Free Radicals and Diseases 290mentioning
confidence: 99%